2002
DOI: 10.1097/00043426-200212000-00010
|View full text |Cite
|
Sign up to set email alerts
|

p53 Expression in Biopsies From Children With Langerhans Cell Histiocytosis

Abstract: An increased expression of p53 in pLC indicates an altered DNA repair control with or without abnormal control of apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 15 publications
5
14
0
Order By: Relevance
“…7 A mutation in gene or inactivation of respective protein would result in the failure of regulation and abnormally high incidence of cells with detectable nuclear p53. 7 Expression of high levels of p53 have been reported in previous studies. 4,7,8 However, the correlation between p53 expression and manifestation of the disease is unclear.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…7 A mutation in gene or inactivation of respective protein would result in the failure of regulation and abnormally high incidence of cells with detectable nuclear p53. 7 Expression of high levels of p53 have been reported in previous studies. 4,7,8 However, the correlation between p53 expression and manifestation of the disease is unclear.…”
supporting
confidence: 52%
“…7 Expression of high levels of p53 have been reported in previous studies. 4,7,8 However, the correlation between p53 expression and manifestation of the disease is unclear.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Lesional Langerhans cells demonstrate several characteristic phenotypic changes that differentiate them from the normal Langerhans cells. Bank et al 15 reported increased expression of wild-type 53 in the lesional Langerhans cells from 50 pathologic specimens, whereas Schouten et al 16 also demonstrated increased expression of MDM2, a negative regulator of p53, as well as p21, p16, Rb, B-cell leukemia/lymphoma 2, and the transforming growth factor A receptor. Although these data point to a possible molecular pathway, the definitive etiology remains an enigma.…”
Section: Pathophysiologymentioning
confidence: 99%
“…This was assessed in at least 8 LCH lesions with and in 8 LCH lesions without BRAFV600E mutation. Because TP53 mutations and subsequent up-regulation of mutant p53 protein have also been discussed as a pathomechanism underlying LCH, 25,26 we assessed p53 expression in the lesions by immunohistochemistry. Strong expression of p53 was seen in LCH independent of BRAFV600E mutational status ( Figure 4F; P Ͼ .19, Student t test).…”
Section: Distribution Of Brafv600e-positive Cells and Activation Of Perkmentioning
confidence: 99%